7x+(5-x)3=12+15

Simple and best practice solution for 7x+(5-x)3=12+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+(5-x)3=12+15 equation:


Simplifying
7x + (5 + -1x) * 3 = 12 + 15

Reorder the terms for easier multiplication:
7x + 3(5 + -1x) = 12 + 15
7x + (5 * 3 + -1x * 3) = 12 + 15
7x + (15 + -3x) = 12 + 15

Reorder the terms:
15 + 7x + -3x = 12 + 15

Combine like terms: 7x + -3x = 4x
15 + 4x = 12 + 15

Combine like terms: 12 + 15 = 27
15 + 4x = 27

Solving
15 + 4x = 27

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + 4x = 27 + -15

Combine like terms: 15 + -15 = 0
0 + 4x = 27 + -15
4x = 27 + -15

Combine like terms: 27 + -15 = 12
4x = 12

Divide each side by '4'.
x = 3

Simplifying
x = 3

See similar equations:

| 2x*3x*4xy= | | 34346920357904578096870945807824507809548709845097824057284507928049578094804380934580982450978109348091834091834709870743+3296834986723986729834769345876x=34576384563837658375687684536-39475298374698374589649537698457896x | | 4=160 | | 1r+8.2+0.4=-8.6 | | 1=0x+1 | | 182.12=2r*3.14 | | -6x-24=-144 | | 8.93/4.44=4.49/n | | 9X=3-6Y | | Y=4f(-x)-23 | | e^4lnx=6 | | 2h^3-18=0 | | 87+91+81+n=90 | | 5-2(3x-5)=-21 | | [-3+10y]=-7(57-y) | | 12/3+12/4+x=22 | | (8x-8)(8x+8)= | | 5/7r=20 | | 6p-4=-12 | | 600=n | | 3h^2+7h-6=0 | | -32z=-64 | | j+w=r | | 7x+42=49 | | 60x^3-150x=0 | | 15-7=14z+12 | | y-0=7 | | z-28=6 | | -490t^2+1470t=980 | | 2x(7)=352 | | -2/5x-6-5 | | 5-0.05x=3 |

Equations solver categories